Introduction to Energy Systems Modelling - Andrea Herbst; Felipe Andrés Toro; Felix Reitze; Eberhard Jochem (Swiss Journal of Economics and Statistics, 2012)
The energy demand and supply projections of the Swiss government funded by the Swiss Federal Office of Energy and carried out by a consortium of institutes and consulting companies are based on two types of energy models: macroeconomic general equilibrium models and bottom-up models for each sector. While the macroeconomic models are used to deliver the economic, demographic and policy framework conditions as well as the macroeconomic impacts of particular scenarios, the bottom-up models simulate the technical developments in the final energy sectors and try to optimise electricity generation under the given boundary conditions of a particular scenario. This introductory article gives an overview of some of the energy models used in Switzerland and – more importantly – some insights into current advanced energy system modelling practice pointing to the characteristics of the two modelling types and their advantages and limitations.
Keywords: C63; L61; 330; energy modelling; bottom-up; top-down; hybrid energy system modelling; Switzerland